2021
DOI: 10.3390/hydrology8040165
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Utility of Satellite-Based and Gauge-Based Gridded Precipitation Products in the Huai Bang Sai Watershed of Northeastern Thailand

Abstract: Accurate rainfall estimates are important in many hydrologic activities. Rainfall data are retrieved from rain gauges (RGs), satellites, radars, and re-analysis products. The accuracy of gauge-based gridded precipitation products (GbGPPs) relies on the distribution of RGs and the quality of rainfall data records obtained from these. The accuracy of satellite-based precipitation products (SbPPs) depends on many factors, including basin climatology, basin topography, precipitation mechanism, etc. The hydrologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Following this requirement, many research studies have been conducted around the world to assess the accuracy and reliability of SRPs with respect to RG data [6,[18][19][20]. Many studies have demonstrated that TRMM (TMPA) is comparatively better than other SRPs since it used available gauge measurements in its calibration process [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Following this requirement, many research studies have been conducted around the world to assess the accuracy and reliability of SRPs with respect to RG data [6,[18][19][20]. Many studies have demonstrated that TRMM (TMPA) is comparatively better than other SRPs since it used available gauge measurements in its calibration process [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Other hydrological models, such as Soil & Water Assessment Tool (SWAT) [68,69], Water Evaluation And Planning System (WEAP) [70] MIKE SHE [71] etc., are recommended to use for the study area to compare with HEC-HMS. Moreover, as a part of a future study, it is recommended to use the JUST and LSWAVE package, which can provide coherency and phase differences results in the time-frequency domain for streamflow and precipitation [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Bias correction techniques can be employed to enhance the accuracy of global satellite precipitation products by incorporating local gauge-based data [13]. This approach proved to be beneficial in simulating streamflow in mountainous catchments [14,15], delivering promising results at both daily and monthly scales. In fact, it surpassed the conventional gauge-only approach [16,17].…”
Section: Introductionmentioning
confidence: 99%